The Effectiveness of Electronic Software in Developing English Language Skills (Listening and Speaking) for the Primary Stage Students in Jordan - Afraa Mohammed Sallam Saif, Fadi Abdul Raheem Odeh Bani Ahmad, (Opción)
The study aimed to investigate the effectiveness of an electronic software in developing English language skills (listening and speaking) for the primary stage students in Jordan. To achieve the objectives of the study, a quasi-experimental approach was used, and the sample was chosen purposefully. The sample consisted of (50) students from the sixth grade of ASamiah International School in the Capital Amman for the second semester of the academic year 2018/2019. The study sample were distributed randomly into two groups: the experimental group which consisted of (25) students who were studied the English language subject using an electronic software, and the control group which consisted of (25) students who were studied the same English language subject in the ordinary way. One instrument was prepared, which was the achievement test (pre & post test) after verified their validity and stability. The results showed that there were statistically significant differences at the level (a=0.05) between the two groups for the benefit of the experimental group in the post-test, which was studied by using the electronic software. The study revealed the effectiveness of electronic software in the development of English language skills (listening and speaking). According to the results, the researcher recommended to use the electronic softwares in schools because of its effectiveness in developing English language skills.